2010 International Conference on Microelectronic Test Structures (ICMTS) 2010
DOI: 10.1109/icmts.2010.5466851
|View full text |Cite
|
Sign up to set email alerts
|

Direct probing of trapped charge dynamics in SiN by Kelvin Force Microscopy

Abstract: In this work, we explore the potential of Kelvin Force Microscopy (KFM) measurements to investigate the lateral charge transport in SiN layers with two different compositions (standard, std, and Silicon rich, Si-rich). The dynamics of the lateral spread of the trapped charge is analyzed with the help of three dimensional numerical device simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…These conclusions are not inconsistent with the findings in [7] and [8], where very similar energy distributions have been proposed for traps in nearly stoichiometric and Si-rich SiN samples. The similar trap energy depth is also in qualitative agreement with KFM measurements of the lateral charge spread in SiN layers [9], [43] and the retention experiments on thick tunnel oxide devices [10]. However, the very small energy difference (≈0.1-0.2 eV) reported for the traps in std and Si-rich SiN films is insufficient to explain the large difference in the retention experiments of the two SiN compositions [see Fig.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These conclusions are not inconsistent with the findings in [7] and [8], where very similar energy distributions have been proposed for traps in nearly stoichiometric and Si-rich SiN samples. The similar trap energy depth is also in qualitative agreement with KFM measurements of the lateral charge spread in SiN layers [9], [43] and the retention experiments on thick tunnel oxide devices [10]. However, the very small energy difference (≈0.1-0.2 eV) reported for the traps in std and Si-rich SiN films is insufficient to explain the large difference in the retention experiments of the two SiN compositions [see Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Although possible corrections to the trap energy depth will be discussed in the following, at this stage, it is worth to note that, since the two defects have similar energy level (within approximately 0.2 eV), they are difficult to discriminate by means of activation energy experiments, as already pointed out in [43]. This evidence is also in qualitative agreement with the results of the KFM measurements in [9] that do not show differences in the detrapping rates of SiN films with different stoichiometries.…”
Section: Electrical Properties Of Sin Defectssupporting
confidence: 83%
See 1 more Smart Citation
“…Vianello, et al, recently reported a work on charge dynamics in silicon nitride based on similar experimental setup, where they focused on electron diffusion dynamics and additional quantification was performed based on numerical simulation [23]. In this work, we provide a more complete description of charge dynamics attainable by EFM, and present analyses on both carriers (electrons and holes) at various temperatures, which was supported by quantification of temperature dependent diffusion coefficients based on a simple analytic model.…”
Section: Scalability Assessment Of Nitride Based Flashmentioning
confidence: 92%
“…This may be problematic because, until recently, it has been continually reported that the lateral charge transport gives a significant effect to the charge retention [13,14]. The lateral migration was proved in many different ways, for example, the direct probing method (AFM) [15,16], electrical measurement [13,17] and theoretical simulation [13]. This lateral leakage cannot be eliminated by separating the nitride region for each cells because of the reliability degradation due to the cutting of the nitride layer [17].…”
Section: Introductionmentioning
confidence: 97%